2D Black Phosphorus/SrTiO3‐Based Programmable Photoconductive Switch. Issue 35 (4th July 2016) - Liu, Fucai; Zhu, Chao; You, Lu; Liang, Shi‐Jun; Zheng, Shoujun; Zhou, Jiadong; Fu, Qundong; He, Yongmin; Zeng, Qingsheng; Fan, Hong Jin; Ang, Lay Kee; Wang, Junling; et al.
Abstract : A novel heterostructure is designed by stacking 2D black phosphorus (BP) on a SrTiO3 substrate . The device demonstrates programmable photoconductive switching under illumination of UV and red light. The light‐tunable persistent photoconductivity exhibits a large on/off ratio exceeding 10 5 . The persistent state shows almost no relaxation or decay at low temperature. These features are suitable for a new generation of optoelectronic devices for memory application.